Digital Communication of Local Governments in Building Public Trust in Sidenreng Rappang Regency - Nurhayati Nurhayati; Abdul Jabbar; Herman Dema; Herman Lawelai (Universitas Pancasakti, 2026)
This research aims to analyze the role of digital communication in building public trust in local governments, with a focus on the Sidenreng Rappang Regency Government. In the context of digital governance, social media serves as a strategic instrument to bridge communication between government and society; however, its effectiveness in fostering public trust remains a challenge. This study employs a qualitative case study approach, utilizing in-depth interviews, observations of official government social media, and document analysis. Data were analyzed using the Miles and Huberman interactive model. The findings reveal that digital communication practices are still dominated by informative approaches that emphasize information dissemination rather than interactive engagement. While this approach contributes to transparency and the formation of cognitive-based trust, it has not been effective in fostering relational trust characterized by responsiveness, integrity, and empathy. A gap also exists between government communication strategies and public expectations, particularly in terms of interaction and participation. Practically, these findings suggest that local governments and public communication managers need to shift from one-way informational communication toward more dialogical and engagement-based strategies. This includes strengthening responsiveness to public feedback, developing interactive content, and adopting more empathetic communication styles. Such improvements are essential to enhance sustainable public trust and ensure the effectiveness of digital governance practices.